Integration of teledentistry in oral health care during COVID-19 pandemic - Neetika Singh; Amina Sultan; Akanksha Juneja; Isha Aggarwal; Tanzin Palkit; Tanvi Ohri (Wolters Kluwer Medknow Publications, 2020)
The COVID-19 pandemic has generated turmoil at all levels. The patients, in particular, are facing a tough time due to the non-availability of physical health care. As everyone is worried about their lives, oral health has taken a back seat. Patients who suffer from dental issues are in a dilemma over available options to address their oral health issues. This is where Teledentistry comes into the picture. Teledentistry is a mode to improve access to oral health services in areas with inadequate availability of general and specialty dental care and is emerging as a practical solution in emergency aid, initial consultation, and expert opinion. In India, several parts of the country lack a sufficient bandwidth or uninterrupted access to the internet facilities, which is also a huge barrier for practicing teledentistry during these pandemic times. Although teledentistry is yet to become an integral part of the oral health-care system in India, nonetheless, COVID times have at least pushed dental practitioners across the country into accepting and using it as an alternative method of dental care. This current pandemic can serve as an opportunity to develop teledentistry on a larger scale, making sure that no individual lacks oral health care, irrespective of the scenarios in the world.